2009
DOI: 10.1111/j.1440-1681.2008.05077.x
|View full text |Cite
|
Sign up to set email alerts
|

Kynurenine Metabolites and Inflammation Markers in Depressed Patients Treated With Fluoxetine or Counselling

Abstract: 1. Depression could result from changes in tryptophan availability caused by activation of the kynurenine pathway as a result of inflammation. In the present study, we examined patients newly diagnosed with depression to determine whether kynurenines and related factors change in parallel with improvements in mood. 2. Concentrations of 5-hydroxytryptamine (5-HT; serotonin), 5-hydroxyindoleacetic acid (5-HIAA), oxidized tryptophan metabolites, brain-derived neurotrophic factor (BDNF) and inflammatory mediators … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
1
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 73 publications
(83 reference statements)
2
33
1
2
Order By: Relevance
“…47 Rodents treated with antipsychotics or antidepressants also failed to show a substantial effect on peripheral KYNA. 1,48,49 We did not find a clear relationship between dose of antipsychotics and salivary KYNA level, nor did salivary KYNA level differ between patients treated vs not treated with antipsychotics. It is therefore unlikely that the pattern of increased KYNA levels in patients with distress intolerance can be explained by effects of antipsychotics.…”
Section: Discussioncontrasting
confidence: 62%
“…47 Rodents treated with antipsychotics or antidepressants also failed to show a substantial effect on peripheral KYNA. 1,48,49 We did not find a clear relationship between dose of antipsychotics and salivary KYNA level, nor did salivary KYNA level differ between patients treated vs not treated with antipsychotics. It is therefore unlikely that the pattern of increased KYNA levels in patients with distress intolerance can be explained by effects of antipsychotics.…”
Section: Discussioncontrasting
confidence: 62%
“…Longitudinal studies with multiple blood draws indicated that the levels of cytokines may significantly fluctuate over the time of treatment which may partially explain the inconsistency of results among presented studies [Hernandez et al, 2013;Mackay et al, 2009]. …”
Section: Accepted Manuscriptmentioning
confidence: 97%
“…We did not include studies measuring the effect of non-pharmacological depression treatments or studies with the use of ketamine or pharmacological agents not registered as antidepressants. We did however partially include some studies (Brunoni et al 2014, Ranjbar et al 2014, Hernandez et al 2014, Abbasi et al 2012, Mackay et al 2009, Jazayeri et al 2010) examining the effect of other than antidepressant therapies with the control group (e.g. treated with an SSRI) meeting our inclusion criteria.…”
Section: Systematic Search and Criteriamentioning
confidence: 99%
“…TRYCATs -Little or no change was observed in the concentrations of any of the TRYCATs following treatment with fluoxetine, fluoxetine plus the thyroid hormone triiodothyronine (T3), or counselling (Mackay et al, 2009). Despite this, in a correlation analysis at weeks 6 and 18, highly significant relationships between several of the TRYCATs and psychiatric inventory scores were revealed.…”
Section: Accepted M Manuscriptmentioning
confidence: 98%